Exploring Indonesia’s Local Wisdom In The 2024 Presidential Campaigns - Ronny Basista; Fatmawati Moekahar; Norhayati Rafida Norhayati Rafida (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2025)
The article explores the significance of local Indonesian wisdom in the 2024 presidential campaigns, particularly on social media. It uses a constructivist paradigm to analyze the interactions of candidates in political campaigns. Data on local wisdom was collected through interviews, focus group discussions, and observation. The research findings suggest that local wisdom values were effectively utilized as a central approach in the 2024 presidential election campaigns on social media, particularly on Instagram. The religious and socio-cultural activities of the Indonesian people exemplify the significance of local wisdom in political campaigns. The local wisdom approach with a socio-cultural orientation strongly resonated with the Indonesian populace, but the exploration of local wisdom values was primarily limited to the use of cultural symbols during the election campaign period.